PENERAPAN MODEL PEMBELAJARAN DISKUSI DENGAN STRATEGI BEACH BALL UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI DAN PEMAHAMAN KONSEP SISWA SMAN 12 SURABAYA - Putri Ayu Rachmawati (PT Innovative Academic Journals, 2024)
This research aims to describe the implementation of the discussion-based learning model with the beach ball strategy, describe the improvement in students' communication skills after using this model, and describe students' conceptual understanding of the topic of work and energy at SMAN 12 Surabaya. This research is a descriptive quantitative research with a pre-experimental design. The design used is a one-group pretest-posttest design, with the subjects being class X MIA 2 (31 students), X MIA 4 (35 students), and X MIA 5 (30 students). The research was conducted over two meetings. The results showed that the implementation of the discussion-based learning model with the beach ball strategy in all three classes was categorized as very good. Students' verbal communication skills improved from the first to the second meeting, with average percentages of 81.11%, 82.78%, and 83.33%. Non-verbal communication skills also showed improvement from the first to the second meeting, with averages of 72.22%, 62.50%, and 72.22%, indicating that communication skills were in the